PUBLIC FOOD PROCUREMENT - A TOOL FOR A SUSTAINABLE ECONOMY DEVELOPMENT IN RURAL AREAS - Ecaterina Milica DOBROTĂ; Alina-Florentina SĂRACU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Annually, the state allocates significant amounts of money for the carrying out of public procurement contracts concerned with the supply of food products. Rural areas, due to their natural potential, but also to their existing human resource, can further develop through the implementation of projects concerned with circular economy and a sustainable food chain. The implementation of Green Deal policies, the integration of appropriate sustainable development strategies will allow the economic growth of rural areas. In the making of this article, information published in the Electronic Public Procurement System (EPPS), during the 2018-2021 period was collected, concerning contracts for the supply of various food products. The novelty of this article consists in the analysis carried out on food related public procurement, by product categories and institutions. Based on the results of this research, there are suggestions for opportunities of development in rural areas, issues related to the sustainability of the food chain which should be integrated in sustainable public procurement procedures.